Technical considerations and outcomes for ileal ureter replacement: a retrospective study in China - Wenlong Zhong (BMC Surgery, 2019)
Abstract Background Ileal ureter replacement is an alternative treatment for various length ureter defects. We present our experience and outcome of ileal ureter replacement in China. Methods We retrospectively collected data of patients who underwent ileal ureter replacement between January 2010 and January 2015. We reviewed the medical history, indications for surgery, operative data, perioperative data, and outcomes. Besides, follow-up data included symptom, urine routine test, serum creatinine, serum electrolyte status, and radiographic test. Results There were 23 patients who underwent ileal ureter replacement by the same surgeon. Twenty patients were performed unilateral ileal ureter replacement, two patients underwent a combination of ileal ureter replacement and Boari flap-psoas hitch, and one received bilateral ileal ureter replacement. Among these patients, the main cause leading to surgical treatment was iatrogenic injuries (n = 15), especially urinary surgery procedure (n = 11). The median follow-up time was 45 months. There were 6 early complications and 6 late complications after operation. Only one patient suffered from small bowel-related complication and was cured by conservative treatment. Only the patient who underwent bilateral ileal ureter replacement had metabolic acidosis. And 22 patients (95.7%) had a good renal function. Conclusions Ileal ureter replacement is an efficacious and safe procedure for the therapy of long ureteral defects. With appropriate technical considerations, the complication rate may decrease.